2017
DOI: 10.1007/s11481-017-9759-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Silymarin, Quercetin and Naringenin Treatments Increase Monoamines Synthesis and Hippocampal Sirt1 Levels Improving Cognition in Aged Rats

Abstract: Polyphenols have beneficial neurological effects delaying cognitive and motor decline in aging due to their antioxidant, antiinflammatory and neuroprotective properties. These effects could be related to SIRT1 activation (implicated in synaptic plasticity, memory and inflammation) and monoaminergic synthesis modulation. In this work, we studied in old male rats, the in vivo effects of long-term administration of different polyphenols (silymarin, quercetin and naringenin; 20 mg/kg/day i.p, 4 weeks) (Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 73 publications
9
62
0
Order By: Relevance
“…Caspase‐3 and caspase‐9 are cysteine protease that are involved in mediating cell apoptosis; once activated, they result in cell shrinkage, DNA degradation, and the formation of apoptotic bodies cascade . It has been shown that INH may expedite physiological apoptosis by decreasing the expression of Bcl‐2, elevating Bax, activating caspase‐9 and caspase‐3 in vivo and in vitro . The findings from the present research were consistent with previous reports and further demonstrated that pretreatment with Que reversed these changes in HepG2 cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Caspase‐3 and caspase‐9 are cysteine protease that are involved in mediating cell apoptosis; once activated, they result in cell shrinkage, DNA degradation, and the formation of apoptotic bodies cascade . It has been shown that INH may expedite physiological apoptosis by decreasing the expression of Bcl‐2, elevating Bax, activating caspase‐9 and caspase‐3 in vivo and in vitro . The findings from the present research were consistent with previous reports and further demonstrated that pretreatment with Que reversed these changes in HepG2 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Quercetin (Que) is a flavonoid compound, ubiquitous in nature, with a variety of biological activities, including antioxidant, scavenging‐free radical, anti‐inflammatory, antitumor, antiapoptosis, and immunosuppressive . Mounting evidence shows that Que could have protective effects on the heart, brain, kidney, liver, and metabolic diseases by targeting the SIRT1 pathway . Besides, research on the regulation of Que on ERK also exists .…”
Section: Introductionmentioning
confidence: 99%
“…Other reports suggested that some of the flavonoids here tested are able to modulate SIRT1, although in other experimental models. NAR treatment was reported to increase SIRT1 expression in both insulin‐resistant L6 myotubes and skeletal muscle of albino Wistar rats (Mutlur Krishnamoorthy & Carani Venkatraman, ) as well as in the hippocampal region of aged rats (Sarubbo et al, ). Oliva and co‐workers demonstrated that the chronic treatment of NRG in ethanol‐fed male Wistar rats increased SIRT1 at both gene and protein level (Oliva et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the combination of dasatinib and quercetin is reported to extend the lives of older people . Quercetin is an SIRT1 activator . Studies have found that quercetin increases monoamine synthesis in aged rats by activating SIRT1 and improves cognitive function in aged rats .…”
Section: Introductionmentioning
confidence: 99%